Pengaruh Motivasi Kerja dan Penghargaan Terhadap Loyalitas Karyawan di XYZ Hotel Bali Uluwatu - Chandra, Agnes; Rastitiati, Ni Kade Juli; Kalpikawati, Ida Ayu (Program Studi Manajemen Divisi Kamar, 2024)
The aim of this research is to analyze the influence of the work motivation and recognition on employee loyalty at XYZ Hotel Bali Uluwatu. The data was collected through the distribution of questionnaires to 63 respondents from various departmentsat XYZ Hotel Bali Uluwatu. The data analysis technique employed include a classical assumption test, a multiple linear regression analysis, determination analysis, correlation analysist, t-test, and F test. The data analysis tool used is the SPSS version 25 program for windows. The result of this research showed that work motivation had a positive and significant effect on employee loyalty with significance value of 0,003 < 0,05. Similarly, the provision of recognition has a positive and significant effect on employee loyalty with significance value of 0,009 < 0,05. Work motivation and recognition simultaneously have a positive and significant effect on employee loyalty with significance value of 0,000 < 0,05 and R2 value of 52,6%. Based on the research findings, it is recommended that XYZ Hotel Bali Uluwatu enhance work motivation and provide additional recognition such as extra wage, bonuses, carrier facilities and the like to increase employee loyalty and attachment at XYZ Hotel Bali Uluwatu.